Rectangular microstrip patch antenna (RMPA) with defected ground structure (DGS) for bandwidth enhancement / Fatma Syazana Zaini - Zaini, Fatma Syazana (2014)
In this paper, a rectangular microstrip patch antenna with defected ground structure (DGS) for wireless application is proposed. A rectangular shaped DGS is simulated using the Computer Simulation Technology (CST) Microwave Studio software to enhance the antenna bandwidth. The simulation results is compared and analyzed. The antennas with rectangular DGS could improve approximately 64% of bandwidth and miniaturize the antenna about 25%.